Curcumin: Total-Scale Analysis of the Scientific Literature - Yeung, Andy Wai Kan; Horbańczuk, Michal; Tzvetkov, Nikolay T; Mocan, Andrei; Carradori, Simone; Maggi, Filippo; Marchewka, Joanna; Sut, Stefania; Dall'Acqua, Stefano; Gan, Ren-You; Tancheva, Lyubka P; Polgar, Timea; et al. (Molecules (Basel, Switzerland), 2019)
The current study aimed to provide a comprehensive bibliometric overview of the literature on curcumin, complementing the previous reviews and meta-analyses on its potential health benefits. Bibliometric data for the current analysis were extracted from the Web of Science Core Collection database, using the search string TOPIC=("curcumin*"), and analyzed by the VOSviewer software. The search yielded 18,036 manuscripts. The ratio of original articles to reviews was 10.4:1. More than half of the papers have been published since 2014. The major contributing countries were the United States, China, India, Japan, and South Korea. These publications were mainly published in journals representing the following scientific disciplines: biochemistry, chemistry, oncology, and pharmacology. There was a significant positive correlation between the total publication count and averaged citations per manuscript for affiliations, but not for countries/regions and journals. Chemicals that were frequently mentioned in the keywords of evaluated curcumin publications included curcuminoids, resveratrol, chitosan, flavonoids, quercetin, and polyphenols. The literature mainly focused on curcumin's effects against cancer, inflammation, and oxidative stress. Cancer types most frequently investigated were breast, colon, colorectal, pancreatic, and prostate cancers.
Keywords: Web of Science; citation analysis; cancer; data mining; Neoplasms; bibliometrie; lidé; Bibliometrics; Data Mining; kurkumin; Humans; biochemistry; VOSviewer; bibliometrics; Software; software; Curcumin; nádory; pharmacology; curcumin